(untitled) (World Conference on Engineering and Technological Sciences, 2026)
This article analyses the occurrence, distribution characteristics and quantitative dynamics of mercury in gas, oil and groundwater deposits located outside the Fergana region, with particular emphasis on the Bukhara region. The migration of mercury through underground fractures, reservoir rocks and hydrocarbon-bearing formations is considered from the perspective of geochemical processes. In addition, the presence of mercury in gas and oil fields is evaluated as an important factor associated with industrial safety, environmental monitoring, corrosion and degradation of technological equipment, and the potential risk of groundwater contamination. The study highlights the regional variation in mercury content and its relationship with geological structure, fracture systems and groundwater movement. The findings of the article have scientific and practical significance for assessing mercury-related risks during the exploitation of oil and gas deposits, improving monitoring systems and developing environmental safety measures.